Review Of Theory And Practice Literature On Women Entrepreneurship In The Tanzanian Construction Industry: Establishing The Missing Link - Sospeter, Nyamagere Gladys; Rwelamila, Pantaleo David; Nchimbi, Mariam; Masoud, Muhsin (Penerbit Universiti Sains Malaysia, 2014)
The paper presents a review of the theoretical and empirical literature on Tanzania women entrepreneurs in the construction industry. It also discusses and argues for the aspects that lead to the requirement for a study on women-specific issues. A systematic literature review approach was applied and the member check strategy was used to minimise the author's bias. The literature involved three aspects: motivational factors for women's entry into business, the current situation of women entrepreneurs and influencing factors for the under-representation of women in the industry. The under-representation of Women Entrepreneurs in the Construction Industry (WECI) in the construction industry is caused by various factors, such as cultural background, choice of business and level of confidence. Moreover, the social structures and cultural systems that reinforce the continued subordination and marginalisation of women have major implications in their motives and involvement in business. Given the barriers faced by WECI today, there is a pressing necessity to initiate gender-sensitive empowerment programmes to enable them to succeed in their endeavours. Based on the existing literature, this paper establishes the missing link and proposes a study to formulate a conceptual framework necessary to help the public and private sector initiatives in boosting women entrepreneurship in the Tanzanian construction industry